Does dexamethasone enhance control of acute cisplatin induced emesis by ondansetron?. Issue 6815 (7th December 1991) - Smyth, J F; Coleman, R E; Nicolson, M; Gallmeier, W M; Leonard, R C; Cornbleet, M A; Allan, S G; Upadhyaya, B K; Bruntsch, U
Abstract : OBJECTIVE--To determine the contribution of dexamethasone to the efficacy of the 5-hydroxytryptamine antagonist ondansetron in control of cisplatin induced nausea and vomiting. DESIGN--Randomised double blind crossover study. SETTING--Two cancer centres in teaching hospitals, one in the United Kingdom and the other in Germany. SUBJECTS--100 patients (53 men and 47 women) new to cisplatin chemotherapy, 84 of whom completed two consecutive courses of chemotherapy. INTERVENTIONS--Patients were given intravenous dexamethasone (20 mg) or physiological saline with intravenous ondansetron 8 mg before cisplatin, then ondansetron 1 mg/h for 24 hours. Oral ondansetron 8 mg was taken three times daily on days 2-6. MAIN OUTCOME MEASURES--Incidence of complete or major control of emesis (0-2 episodes in the 24 hours after chemotherapy). RESULTS--Complete or major control was obtained in 49 out of 71 (69%) of patients after receiving ondansetron plus dexamethasone compared with 40 out of 71 (56%) when they were given ondansetron alone (p = 0.012). This effect was most pronounced in the first 12 hours after chemotherapy. Patients receiving the combination also had significantly less nausea. Of the 53 patients who expressed a preference, 38 (72%) preferred the combination treatment (p = 0.002) to ondansetron alone. The effect of ondansetron on delayed emesis was less pronounced. CONCLUSIONS--Dexamethasone makes a significant contribution to the efficacy of ondansetron in the control of acute platinum induced emesis.